A Contextualized Social Transformation and Universalism: A Quest for a Mutual Humanization - Hiroko Fukazawa (Canadian Society for Studies in Education, 2008)
Freire (1998, 2005) claimed that the current definition of humanity has been manipulated and objectified in the manner which advances the dominant group's perspective and interests. Drawing mainly upon his claim, it is explained in this article that the current state of social inequality and environmental degradation derives from the definition of humanity; therefore, it is necessary to refine the definition to solve these problems. In restoring a true humanity of everyone, Freire valued contextual differences as an essential feature of human knowledge and denied the existence of a universal human nature; however, the belief in the existence of a universal human nature may provide the incentive necessary for mutual agreement on what is meant by a truly human society.